PERANCANGAN KNOWLEDGE MANAGEMENT SYSTEM BERBASIS WEB (Studi Kasus Konsultasi Tugas Akhir Mahasiswa) - Daniel Oktodeli Sihombing (Universitas Bina Sarana Informatika, 2014)
Students will carry out the final level where the final project is a graduation requirement that students were entitled to a diploma in that field . In the implementation of the final project , students are required to consult the counselor that the final work done properly and on time . Problems experienced are often the least appropriate time to meet and consult on the development of the final project of the student . Many things such as what to do ? how to get started ? What kind of references that should be used ? Being the questions most frequently asked by the final year students in starting work on their final project . Web-based system is a computerized system that uses the Internet medium as a solution to the problems of time and place . Web is a medium that can be accessed by the user with an interface that is structured according to the needs of the user . Knowledge managmenet system ( KMS ) using Nonaka SECI model in its development , so that the transformation procedure tacit knowledge into explicit knowledge becomes clear and tersturktur . KMS is a solution to the lack of proper time for consultation to students , knowledge sharing and knowledge repositories so expect their final project can be completed on time .Keyword: Knowledge Management System, Nonaka SECI Model